Small fish eat smaller fish: A model of interaction strength in early life stages of two tuna species. Issue 3 (21st May 2022) - Ottmann, Daniel; Reglero, Patricia; Alemany, Francisco; Alvarez‐Berastegui, Diego; Martín, Melissa; Fiksen, Øyvind
Abstract: Fish larvae are rarely a major driver of fish mortality, but tunas can produce large batches of larvae that rapidly develop the capacity to kill other fish. We combine a model for the killing potential from Atlantic bluefin tuna (BFT) larvae on larval albacore (ALB) with field observations at a major spawning ground. Both species spawn from June to August, but BFT has a narrow spawning peak at the beginning of the season that results in priority effects. Our model shows that, following a recent stock recovery, BFT larvae have increased their killing pressure, leaving areas of up to 1000 km 2 with < 1% chance of ALB daily survival. Such increase in killing pressure suggests larval ALB has reduced chances to survive; yet in large areas with few BFT, other drivers of early survival prevail over BFT predation. This shows that strong predatory interactions can occur during larval stages in some fishes.